IMPLEMENTATION OF SHARIA MANAGEMENT IN MICRO WAQF BANKS ON COMMUNITY WELFARE CASE STUDY IN INDONESIA AND MALAYSIA - Toni Hidayat; Ahmad Murshidi Musthapa; Siti Maziah Binti Ad Rahman; Anwar Sadat Harahap; Ratna Sari Dewi; Clarisa Tarigan (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research is expected to provide an up-to-date description of the implementation of sharia management at Micro Waqf Banks in improving community welfare. The results of this study can be used as material for consideration by companies to develop appropriate management strategies. Management functions include planning, organizing, actuating, controlling. Planning is a process and series of activities to set goals in advance at a certain time or period and the stages or steps that must be taken to achieve certain goals. Organizing is a process and activity in the division of labor planned by members of the group, determining good work relationship between them, and providing a conducive work environment and facilities. Actuating, namely a series of activities to provide instructions from superiors to subordinates or to people who are organized in formal groups to achieve common goals. Controlling, namely supervision of every activity that is done so that it is in accordance with the plan. The concept of sharia management is universal and comprehensive. Therefore, the paradigm that is built in syari'ah management theory is the activity of thinking, planning, leading and controlling an organization to achieve the goal of maqasid syari'ah, namely realizing the benefit of all mankind. The long-term goal of this research is to contribute to Micro Waqf Banks in their roles, namely: The role of micro waqf banks through the application of sharia management to improve the welfare of the poor who do not have access to formal finance.